2019
DOI: 10.1136/jclinpath-2018-205544
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prognostic analysis for triple-negative breast cancer with metaplastic and invasive ductal carcinoma

Abstract: AimsTriple-negative breast cancer comprises different histological subtypes, including metaplastic breast cancer (MBC) and ductal carcinomas (IDCs). The purpose of this study was to compare triple-negative MBC (TN-MBC) with triple-negative IDC (TN-IDC) in terms of survival and predictive factors.MethodsWith access to the Surveillance, Epidemiology and End Result (SEER) database, a total of 19 383 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 31 publications
4
40
2
1
Order By: Relevance
“…However, there were only 24 and 29 patients in the MBC groups in the aforementioned two studies respectively, which limited representation of the study participants to the entire population of MBC. In recent years, several population-based studies have indicated that there appears to be lower disease-specific survival in MBC patients compared to IDC patients [10][11][12] . In our study, we used a large cohort to compare the outcomes between MBC and IDC diagnosis, and our results are consistent with the findings from previous population-based studies [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there were only 24 and 29 patients in the MBC groups in the aforementioned two studies respectively, which limited representation of the study participants to the entire population of MBC. In recent years, several population-based studies have indicated that there appears to be lower disease-specific survival in MBC patients compared to IDC patients [10][11][12] . In our study, we used a large cohort to compare the outcomes between MBC and IDC diagnosis, and our results are consistent with the findings from previous population-based studies [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…According to our review, its prognosis was worse not only when compared with conventional invasive ductal carcinomas, but also when compared with other TNBC. We reviewed 8 series comparing survival between patients with MBC and TNBC [ 21 , 22 , 24 , 25 , 26 , 62 , 63 , 64 ]. These series included a total of 2,007 MBC and 41,937 TNBC.…”
Section: Mbc Prognosismentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) database, funded by the National Cancer Institute (NCI), has been broadly applied in cancer research and used to explore developments in rare cancers, secondary malignancies, epidemiology, treatments, and outcomes [11,12]. The incidence, prevalence, and survival information on cancers in the database were collected from U.S. cancer registries, and the database has been utilized for thousands of studies, including those on colorectal cancer [13], non-small cell lung cancer [14], gastric cancer [15], and breast cancer [16]. Recently, it has been reported that marital status can independently predict the survival of patients with various cancers, such as colorectal cancer [17], gastric cancer [18,19], nasopharyngeal carcinoma [20], and liver cancer [21].…”
Section: Introductionmentioning
confidence: 99%